2005
DOI: 10.1002/pros.20303
|View full text |Cite
|
Sign up to set email alerts
|

Antisense Bcl-2 sensitizes prostate cancer cells to radiation

Abstract: BACKGROUND-Bcl-2 is anti-apoptotic and overexpression is associated with prostate tumor aggressiveness. We hypothesized that Bcl-2 has a role in prostate cancer radiation (RT) response. The relationship of Bcl-2 expression in four prostate cancer cell lines, and the effect of modulating expression with a Bcl-2 antisense oligonucleotide (G3139, Genasense ® , oblimersen sodium, Genta Incorporated), to RT was examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 33 publications
2
35
0
Order By: Relevance
“…Androgen deprivation treatment causes an increase in Bcl-2 expression (1 -4), and the overexpression of Bcl-2 is associated with the development of androgen independence (1,5,6). Our in vitro studies also show Bcl-2 suppression by antisense Bcl-2 sensitizes prostate cancer cells to radiation (7).…”
supporting
confidence: 56%
“…Androgen deprivation treatment causes an increase in Bcl-2 expression (1 -4), and the overexpression of Bcl-2 is associated with the development of androgen independence (1,5,6). Our in vitro studies also show Bcl-2 suppression by antisense Bcl-2 sensitizes prostate cancer cells to radiation (7).…”
supporting
confidence: 56%
“…BPH-1 and PC3 cells were grown as described (67,68). Monocytes were obtained from the University of California, Los Angeles (UCLA) Virology Core in Iscove's modified Dulbecco's medium (Invitrogen) + 5% (vol/vol) human antibody serum + 15% (vol/vol) FBS and used the same day for experiments.…”
Section: Methodsmentioning
confidence: 99%
“…55 This observation is of particular importance taking into account the promising clinical studies on oblimersen sodium (antisense bcl-2) and the strong experimental evidence of its potent radiosenistizing properties in prostate cancer. 58,59 Human glioblastoma multiforme cells. Recently, it was shown that autophagy is responsible for the death of glioma cells in response to various anticancer agents, including temozolomide, rapamycin, tamoxifen and arsenic trioxide.…”
Section: Autophagy and Cancer Cellsmentioning
confidence: 99%